PANJANG MULUD TRADITION AS A MEDIUM OF SOCIAL COMMUNICATION - Abdul Malik; Liza Diniarizky (al-Balagh : Jurnal Dakwah dan Komunikasi, 2023)
The Panjang Mulud tradition in Serang, Banten is one of the traditions that aims to pay homage and a form of happiness for the birth of the Prophet Muhammad SAW. This tradition is meant as a feeling of gratitude for all the pleasures of life, as well as an effort by the community to tighten the social relations between one another. This study aims to examine social communication that occurs in the Panjang Mulud tradition and the meaning of social action in it for supporting a harmonious social life. This research was conducted through a qualitative approach of ethnomethodology. The data was collected through observation, interviews, and documentation triangulation. Moreover, data analysis was carried out through data reduction, data presentation, and conclusions, which were then analyzed by relating social action theory with the social communication concept. Based on data findings, it was concluded that Panjang Mulud is a space created consciously to reinforce their religious and cultural identity. The activities in the Panjang Mulud tradition are believed to be a form of social action carried out consciously and more value-oriented compared to other motives.